Feasability of a self rehabilitation programm for the upper limb strocke patients in Benin - NIAMA NATTA, DIDIER; ALAGNIDE, HOUNTONDJI ETIENNE; KPADONOU GODONOU, TOUSSAINT; STOQUART, GAETAN; DETREMBLEUR, CHRISTINE; LEJEUNE, THIERRY (My University, 2015)
.....
Keywords: strocke; rehabilitation; self rehabilitation programm; upper limb